Nb–Ta mobility and fractionation during exhumation of UHP eclogite from southwestern Tianshan, China. (15th May 2016) - Zhang, Lijuan; Zhang, Lifei; Lü, Zeng; Bader, Thomas; Chen, Zhenyu
Graphical abstract: Highlights: The rutile core-rim profile of Nb–Ta concentrations in vein has been found in eclogite from southwestern Tianshan UHP belt. The rutile-bearing veins formed by the dehydration reactions of lawsonite during exhumation. The Nb–Ta fractionation can happen during the exhumation of subducted slab. Abstract: In order to study the behavior of high field strength elements (HFSE) during retrograde overprint of ultrahigh-pressure (UHP) eclogites, analysis of Nb and Ta concentrations was carried out on bulk rock, rutile (in both veins and host rocks) and titanite in the host eclogite. The studied samples were collected from the UHP metamorphic belt of southwestern Tianshan, China. Petrographic observation and phase equilibria modeling show that the host eclogites have experienced UHP metamorphism and the rutile-bearing veins are thought to be originated from an internal fluid source, probably by lawsonite dehydration during exhumation. The presence of vein rutile indicates HFSE could be mobilized from host eclogites to veins, which is probably facilitated by complexation with dissolved Na–Al silicates and fluorine-rich fluids. Changes in fluid composition (e.g., F −1, X (CO2) ) may trigger the precipitation of rutile. Rutile/fluid partitioning may be the key to fractionating Nb and Ta, with preference for Ta in the fluid, resulting in Nb/Ta ratio of rutile in the veins lower than that in the host eclogite. Besides, the transformation of rutile into titanite also might be an effective mechanism for fractionating Nb from Ta, resulting in the intra-grain Nb–Ta zonations in vein rutile. The Nb–Ta mobility and fractionation can happen during exhumation of the UHP eclogite, which should be very important for understanding the behavior of HFSE in subduction zone metamorphism.